Swelling potential and swelling pressure calculation methods: A comprehensive review - Ibrahim, Hawkar; Hummadi, Rizgar (Edelweiss Applied Science and Technology, 2025)
Expansive soils, characterized by volume changes due to variations in water content, significantly affect geotechnical engineering. Proper assessment of swelling potential and swelling pressure is essential for improving foundation design on expansive soils, enabling a reduction in risks arising from soil expansion. Different methods for measuring and calculating swelling potential and swelling pressure have been developed, ranging from empirical to analytical approaches, many of which are based on laboratory tests and analysis of soil properties. The paper presents a new classification of these methods, categorizing them into qualitative, semi-qualitative, and quantitative methods. Indirect methods of swell classification are qualitative and semi-qualitative approaches, which may be either single or multi-index methods. In contrast, quantitative approaches are direct methods based on laboratory or field test results. This review will provide researchers and engineers with an easy evaluation of the expansion potential of expansive soils using various methods.